Clinical application of the GLOBE and United Kingdom‐primary biliary cholangitis risk scores in a trial cohort of patients with primary biliary cholangitis. Issue 6 (19th April 2018) - Carbone, Marco; Harms, Maren H.; Lammers, Willem J.; Marmon, Tonya; Pencek, Richard; MacConell, Leigh; Shapiro, David; Jones, David E.; Mells, George F.; Hansen, Bettina E.
Abstract : The GLOBAL Primary Biliary Cholangitis (PBC) Study Group and United Kingdom‐PBC (UK‐PBC) Consortium have demonstrated that dichotomous response criteria are not as accurate as continuous equations at predicting mortality or liver transplantation in PBC. The aim of this analysis was to assess the clinical utility of the GLOBE and UK‐PBC risk scores using data from POISE, a phase 3 trial investigating obeticholic acid (OCA) in patients with PBC. Data (N = 216) at baseline and month 12 were used to calculate the GLOBE and UK‐PBC risk scores to assess the projected change in risk with OCA versus placebo. Additionally, the benefit of OCA was assessed in patients not meeting the POISE primary endpoint. Both the GLOBE and UK‐PBC risk scores predicted a significant reduction in long‐term risk of death and liver transplantation after OCA treatment ( P < 0.0001). The differences in the relative risk reduction from baseline in the 10‐year event risk after 1 year for OCA 10 mg versus placebo was 26% (GLOBE) and 37% (UK‐PBC). The scores also predicted a significantly decreased risk in patients treated with OCA who did not meet POISE response criteria after 1 year of treatment compared to an increased risk with placebo ( P < 0.0001). Conclusion: This analysis demonstrates the use of the GLOBE and UK‐PBC risk scores to assess risk reduction of a cohort treated with OCA. While validation of this risk reduction in studies with clinical outcomes is needed, this study highlights the potential use of these scores in individualizing risk prediction in PBC both in clinical practice and therapeutic trials. ( Hepatology Communications 2018;2:683‐692)